The Impact of the Use of Soft Power in Social Media on Public Diplomacy for International Co-existence - Kaleem, Mahmoud (International Journal of Membrane Science and Technology, 2023)
Social media has become a game changer fundamentally in the way that it connects citizens, governments, and their ideas and voices across geographical divides. The policy process today requires decision making, feedback mechanisms, and quality input to be successful. Thus, social media presents itself as a quality instrument for incorporating a multitude of ideas, opinions, and voices for different stages of policy processes. This means that citizen engagement, which is crucial in policy making becomes easier via social media. However, social media also presents new challenges for soft power. The fast-paced nature of social media means that misinformation and fake news can quickly spread, which can undermine efforts to build relationships and promote understanding between countries. In addition, some countries use social media to spread propaganda, fake news, and extremist ideologies, which can also damage their soft power. This study examines the impact of the use of soft power in social media on public diplomacy for international co-existence in the context of the Middle East and Africa. The alternate methods of soft power include information and gathering data. For instance, social media is a great source of data and gathering information. Countries can achieve their objectives by attracting and persuading others to adopt their values and interests, rather than through coercion or force. Soft power is the ability to influence others through attraction and persuasion, rather than through threats or payment. The proliferation of social media such as YouTube, Facebook, and Twitter present powerful and new communication tools that are capable of influencing policy decisions by channelizing the political opinions of the masses. The upstart of social media and its engagement with the masses have influenced policy as well as politics which can be demonstrated in the Middle East. The Middle East, for instance, has been rife with regimes that have taken advantage of the region’s cultural, linguistic, and religious connections to shape the political environment. In addition, social media has also given voice to previously marginalized groups, particularly youth, women, and minorities, who have used these platforms to advocate for their rights and amplify their voices. This has created new opportunities for public diplomacy, as governments and civil society organizations can engage with these groups and build relationships with them. This study aims to look at the relationship between social media and public diplomacy and identify opportunities and challenges social media networks pose for international coexistence in the context of past and present events from the perspective of both policymakers and scholars. Furthermore, the public diplomacy process and the use of social media as a soft power have been analyzed through a framework and discussed further for a better understanding of the variables. involved.